ROS production in brown adipose tissue mitochondria: the question of UCP1-dependence - Shabalina, Irina G; Vrbacký, Marek; Pecinová, Alena; Kalinovich, Anastasia V; Drahota, Zdeněk; Houštěk, Josef; Mráček, Tomáš; Cannon, Barbara; Nedergaard, Jan (Biochimica et biophysica acta, 2014)
Whether active UCP1 can reduce ROS production in brown-fat mitochondria is presently not settled. The issue is of principal significance, as it can be seen as a proof- or disproof-of-principle concerning the ability of any protein to diminish ROS production through membrane depolarization. We therefore undertook a comprehensive investigation of the significance of UCP1 for ROS production, by comparing the ROS production in brown-fat mitochondria isolated from wildtype mice (that display membrane depolarization) or from UCP1(-/-) mice (with a high membrane potential). We tested the significance of UCP1 for glycerol-3-phosphate-supported ROS production by three methods (fluorescent dihydroethidium and the ESR probe PHH for superoxide, and fluorescent Amplex Red for hydrogen peroxide), and followed ROS production also with succinate, acyl-CoA or pyruvate as substrate. We studied the effects of the reverse electron flow inhibitor rotenone, the UCP1 activity inhibitor GDP, and the uncoupler FCCP. We also examined the effect of a physiologically induced increase in UCP1 amount. We noted GDP effects that were not UCP1-related. We conclude that only ROS production supported by exogenously added succinate was affected by the presence of active UCP1; ROS production supported by any other tested substrate (including endogenously generated succinate) was unaffected. This conclusion indicates that UCP1 is not involved in control of ROS production in brown-fat mitochondria. Extrapolation of these data to other tissues would imply that membrane depolarization may not necessarily decrease physiologically relevant ROS production. This article is a part of a Special Issue entitled: 18th European Bioenergetics Conference (Biochim. Biophys. Acta, Volume 1837, Issue 7, July 2014).
Keywords: Animals; Hydrogen Peroxide; Superoxides; Adipose Tissue, Brown; hnědá tuková tkáň; Glycerophosphates; kyselina jantarová; guanosindifosfát; Mitochondria; Membrane Potential, Mitochondrial; Mice, Knockout; myši knockoutované; Succinic Acid; Carbonyl Cyanide p-Trifluoromethoxyphenylhydrazone; Oxygen Consumption; peroxid vodíku; kyselina pyrohroznová; Reactive Oxygen Species; mitochondriální proteiny; superoxidy; protonové ionofory; Cold Temperature; Immunoblotting; Electron Spin Resonance Spectroscopy; Pyruvic Acid; mitochondrie; iontové kanály; Ion Channels; Male; membránový potenciál mitochondrií; reaktivní formy kyslíku; karbonylkyanid-p-trifluormethoxyfenylhydrazon; elektronová paramagnetická rezonance; imunoblotting; zvířata; mužské pohlaví; Mice, Inbred C57BL; nízká teplota; Mitochondrial Proteins; Guanosine Diphosphate; glycerolfosfáty; Proton Ionophores; spotřeba kyslíku; myši inbrední C57BL